(untitled) (European Journal of Marketing and Economics, 2026)
This study investigates the economic implications of managerial personality traits on leadership effectiveness within Serbia’s evolving business landscape. Analyzing survey data from 160 Serbian managers across hierarchical levels and sectors using the Serbian NEO Personality Inventory and Multifactor Leadership Questionnaire, we demonstrate significant relationships between personality dimensions and leadership styles. Extraversion emerges as a strong positive predictor of transformational leadership (β = 0.42, p < 0.01), suggesting that more extroverted managers excel in inspirational and visionary leadership roles. Conversely, neuroticism shows a negative association with leadership effectiveness (β = -0.31, p < 0.05), potentially impairing decision-making under pressure. Conscientiousness significantly influences transactional leadership approaches (β = 0.38, p < 0.01), highlighting its role in structured, goal-oriented management. Perhaps most notably, managers scoring low in agreeableness demonstrate greater tendencies toward laissez-faire leadership (β = -0.27, p < 0.05), which may lead to passive management styles. These findings carry important economic implications for organizational performance in transitional economies. The demonstrated personality-leadership linkages suggest that personality-aware HR strategies could optimize leadership development programs and managerial selection processes. Specifically, our results indicate that cultivating transformational leadership potential in extroverted candidates while providing targeted support for neuroticism-related challenges may enhance organizational outcomes. The study contributes to leadership economics literature by empirically validating personality-based approaches in the under-researched Serbian context, offering actionable insights for both academic research and business practice.